Current therapeutical strategies for allergic rhinitis. (2nd January 2019) - Klimek, Ludger; Sperl, Annette; Becker, Sven; Mösges, Ralph; Tomazic, Peter Valentin
ABSTRACT: Introduction : Allergic rhinitis is a common condition with increasing prevalence and is associated with several comorbid disorders such as bronchial asthma and atopic dermatitis. If allergen avoidance is not possible, allergen-specific immunotherapy is the only causal treatment option. Areas covered : This review focuses on current treatments and the future outlook for allergic rhinitis. Pharmacotherapy includes mast cell stabilizers, antihistamines, glucocorticosteroids (GCSs), leukotriene receptor antagonists, and nasal decongestants. Nasal GCSs are currently regarded as the most effective treatment and are considered first-line therapy together with non-sedating antihistamines. The new formulation MP29-02 combines the nasal GCS fluticasone propionate with azelastine in one single spray and has achieved greater improvements than those under monotherapy with modern GCSs or antihistamines. Furthermore, this review discusses allergen immunotherapy alone and in combination with modern monoclonal antibodies. Expert opinion : Despite the variety of medications for allergic rhinitis, ranging from general symptomatic agents like GCSs or decongestants, to more specific ones like histamine receptor or leukotriene blockers, to causal therapy like immunotherapy, many patients still experience treatment failures or unsatisfactory results. The ultimate goal may be to endotype every downstream pathway separately in order to offer patients individualized, targeted therapy with specific antibodies against the respective pathway.